Fuel cell gas diffusion layer and preparation method thereof

Through the picosecond laser photosynthesis and microporous layer coating, the problems of insufficient conductivity and uneven surface of the fuel cell gas diffusion layer are solved, which significantly improves the conductivity and surface flatness, and reduces the risk of the proton exchange membrane being pierced.

CN119833665APending Publication Date: 2025-04-15UNILIA (SHANGHAI) FUEL CELLS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510029853.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing fuel cell gas diffusion layers (GDLs) have shortcomings in electrical conductivity and surface flatness, resulting in increased contact resistance and risk of puncture of proton exchange membranes.

Method used

The two surfaces of the gas diffusion backing layer were light-finished by using picosecond laser to remove excess polytetrafluoroethylene on the surface, reduce surface roughness, and coat the microporous layer slurry on the surface after photofinishing, and dry and sintered.

Benefits of technology

It significantly reduces the contact resistance of the gas diffusion layer, improves the conductivity, reduces the exposure of carbon fibers on the surface of the microporous layer, reduces the risk of the proton exchange membrane being pierced, and maintains the overall thickness and mass transfer ability of the gas diffusion layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833665A_ABST
    Figure CN119833665A_ABST
Patent Text Reader

Abstract

The invention provides a fuel cell gas diffusion layer and a preparation method thereof, and relates to the technical field of fuel cells, and the method comprises the following steps: carrying out finishing processing on two opposite surfaces of a gas diffusion backing layer by adopting picosecond laser; one surface of the gas diffusion backing layer subjected to finishing processing is coated with micropore layer slurry; and drying and sintering the gas diffusion backing layer coated with the microporous layer slurry to obtain the gas diffusion layer. Wherein the output power of the picosecond laser ranges from 0.4 KW to 1.6 KW. Excessive PTFE on the surface of the gas diffusion backing layer is removed through the photoacoustic effect of picosecond laser, the surface F element content and the surface roughness are reduced on the premise that the structure of the gas diffusion backing layer is not damaged, the conductivity is improved, and the problem that carbon fibers on the surface of the microporous layer are exposed is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a fuel cell gas diffusion layer and a preparation method thereof. Background Art

[0002] The gas diffusion layer (GDL) is an important component of the membrane electrode of fuel cells and hydrogen production equipment, and its conductive properties directly affect the overall performance of the membrane electrode. The GDL in the prior art is usually composed of carbon fiber paper (GDB) and microporous layer (MPL), in which the GDB needs to be impregnated with polytetrafluoroethylene (PTFE) solution for hydrophobic treatment to improve its drainage capacity, thereby improving the performance of the membrane electrode at high current density.

[0003] However, PTFE, as a (C2F4) n The fluoropolymer with a structure has a very weak intermolecular bonding force, and the mutual repulsion between F atoms causes the PTFE molecular chain to be arranged in a spiral shape. This characteristic makes the distribution of PTFE solution on carbon fiber often uneven, especially the concentration on the surface of GDB is significantly higher than that inside it. Since PTFE itself is an insulating material, its agglomeration on the surface of GDB will increase the contact resistance between GDB and the adjacent bipolar plate, thereby reducing the performance of the membrane electrode.

[0004] On the other hand, during the preparation of GDL, since the roughness of the GDB surface is higher than that of MPL, when the MPL slurry is coated on the GDB and dried, the GDB carbon fibers are often exposed on the MPL surface. These exposed carbon fibers may penetrate the thinner catalytic layer, significantly increasing the risk of the proton exchange membrane being punctured. Once the proton exchange membrane is punctured, not only will the performance of the single cell drop sharply, it may even burn through the membrane electrode, causing the entire stack to fail to work properly.

[0005] In order to solve the problem of exposed carbon fibers on the MPL side, the existing technology has proposed a solution of increasing the thickness of the MPL. Although this method can cover more exposed carbon fibers to a certain extent, the increase in the thickness of the MPL will also extend the path of gas transmission from the flow field to the catalyst layer, resulting in increased gas mass transfer resistance and ultimately reducing the performance of the fuel cell. Therefore, simply increasing the thickness of the MPL is not an ideal solution.

[0006] At present, laser heat treatment technology is mainly used for surface treatment of GDB. This technology uses a focused high-power density laser beam to rapidly melt, vaporize, ablate or reach the ignition point of the irradiated carbon fiber area, and at the same time uses a high-speed airflow coaxial with the beam to blow away the molten material to achieve surface treatment or cutting of GDB. However, the heat generated by this method during the cutting process will have a thermal impact on the surrounding materials, destroy the structure of GDB, and thus affect the performance of GDL. Summary of the invention

[0007] The object of the present invention is to provide a fuel cell gas diffusion layer and a preparation method thereof, which can reduce the PTFE content on the surface of GDB to improve its conductivity and improve its surface flatness to reduce the problem of exposure of carbon fibers in the MPL layer without affecting the overall thickness and mass transfer capacity of GDL.

[0008] To achieve the above object, the present invention is implemented through the following technical solutions:

[0009] A method for preparing a fuel cell gas diffusion layer comprises the following steps:

[0010] S1: using picosecond laser to perform finishing processing on the first surface of the gas diffusion backing layer;

[0011] S2: performing finishing processing on the second surface of the gas diffusion backing layer using a picosecond laser, wherein the second surface is arranged opposite to the first surface;

[0012] S3: coating a microporous layer slurry on at least one surface of the gas diffusion backing layer that has been subjected to finishing processing;

[0013] S4: drying and sintering the gas diffusion backing layer coated with the microporous layer slurry to obtain the gas diffusion layer.

[0014] Furthermore: in step S1 and step S2, the output power of the picosecond laser is controlled to be 0.4KW-1.6KW.

[0015] Furthermore: the number of scans of the picosecond laser in step S1 and step S2 is 1.

[0016] Furthermore: the microporous layer slurry in step S3 includes deionized water, carbon powder, polytetrafluoroethylene emulsion and dispersant.

[0017] Further: the step of preparing the microporous layer slurry comprises:

[0018] S31: mixing the deionized water, carbon powder, polytetrafluoroethylene emulsion and dispersant and performing ultrasonic treatment;

[0019] S32: dispersing and stirring the mixture after ultrasonic treatment.

[0020] Furthermore: the ultrasonic treatment time in step S31 is 2 minutes, and the dispersion stirring time in step S32 is 30 minutes.

[0021] Furthermore: the drying temperature in step S4 is 80° C. and the drying time is 30 minutes.

[0022] Furthermore: the sintering temperature in step S4 is 350° C. and the sintering time is 40 minutes.

[0023] The present invention also provides a gas diffusion layer prepared according to the above method, the gas diffusion layer comprising a gas diffusion backing layer and a microporous layer arranged on the surface of the gas diffusion backing layer, wherein: the surface F content of the gas diffusion backing layer is less than 25%, and the surface roughness is less than 7 microns; the surface of the microporous layer has no exposed carbon fibers

[0024] Compared with the prior art, the present invention uses picosecond laser to perform finishing processing on the two surfaces of the gas diffusion backing layer, which has the following beneficial effects:

[0025] 1. Remove excess PTFE on the surface of the gas diffusion backing layer through the photoacoustic effect of picosecond laser, reduce the F element content on its surface from 25.11% to about 15%, and significantly increase the exposure of the surface carbon fiber. At the same time, due to the extremely short action time of picosecond laser, it is possible to achieve surface modification without destroying the structure of the gas diffusion backing layer, keeping its thickness unchanged at about 145 microns. This treatment method not only reduces the contact resistance between the gas diffusion layer and adjacent components, improves the electrical conductivity, but also ensures the structural integrity of the gas diffusion backing layer.

[0026] Second, through the precise processing of picosecond laser, the surface roughness of the gas diffusion backing layer is reduced from 7.15 microns to about 4.5 microns. The reduction of surface roughness enables the subsequently coated microporous layer to better fit the gas diffusion backing layer, effectively solving the problem of carbon fiber exposure on the surface of the microporous layer, thereby reducing the risk of proton exchange membrane puncture. Compared with the solution of increasing the thickness of the microporous layer in the prior art, the present invention solves the problem of carbon fiber exposure without affecting gas mass transfer.

[0027] 3. The preparation method provided by the present invention can simultaneously solve the two key technical problems of insufficient electrical conductivity of the gas diffusion layer and exposure of carbon fibers in the microporous layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the structure of the gas diffusion layer;

[0029] Figure 2 It is a schematic flow chart of a method for preparing a gas diffusion layer for a fuel cell;

[0030] Figure 3 This is the result of analyzing the F element content on the surface of different samples using an energy spectrometer;

[0031] Figure 4 The results of observing the surface morphology of the microporous layer of different samples using an optical microscope;

[0032] In the figure:

[0033] 1. Gas diffusion backing layer; 2. Microporous layer. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0036] like Figure 1 As shown, the gas diffusion layer of the present invention comprises a gas diffusion backing layer and a microporous layer arranged on the surface of the gas diffusion backing layer. The gas diffusion backing layer is composed of carbon fibers, and a polytetrafluoroethylene hydrophobic layer is coated on its surface. When preparing the gas diffusion layer, the gas diffusion backing layer needs to be surface treated first to reduce the polytetrafluoroethylene content on the surface and improve the surface roughness.

[0037] Specifically, picosecond laser is used to finish the gas diffusion backing layer. Picosecond laser is a laser with an output pulse width at the picosecond level. Its working principle is to reach a high power in a very short time, so that the material absorbs energy and then, through the photoacoustic effect and other effects, the material is crushed into very fine particles and removed. Compared with traditional laser heat treatment, picosecond laser has the characteristics of short action time and high precision, which can effectively avoid problems such as thermal deformation and thermal damage.

[0038] The surface treatment of the gas diffusion backing layer includes the following steps: first, the first surface of the gas diffusion backing layer is facing upward, and it is scanned using a picosecond laser device. The output power of the laser is controlled between 5% and 20% of the maximum output power of the laser device, and the number of scans is 1. Then, the gas diffusion backing layer is turned over so that its second surface faces upward, and the same laser parameters are used for scanning.

[0039] The above is a brief introduction to the present invention. The method for preparing a fuel cell gas diffusion layer of the present invention is described in detail below through specific embodiments.

[0040] A method for preparing a fuel cell gas diffusion layer, such as Figure 2 As shown, the following steps are included:

[0041] S1: using picosecond laser to perform finishing processing on the first surface of the gas diffusion backing layer;

[0042] S2: performing finishing processing on the second surface of the gas diffusion backing layer using a picosecond laser, wherein the second surface is arranged opposite to the first surface;

[0043] S3: coating a microporous layer slurry on at least one surface of the gas diffusion backing layer that has been subjected to finishing processing;

[0044] S4: drying and sintering the gas diffusion backing layer coated with the microporous layer slurry to obtain the gas diffusion layer.

[0045] In some embodiments, in step S1 and step S2, the output power of the picosecond laser is controlled to be 0.4KW-1.6KW.

[0046] The number of scans of the picosecond laser in step S1 and step S2 is 1. The microporous layer slurry in step S3 includes deionized water, carbon powder, polytetrafluoroethylene emulsion and a dispersant.

[0047] In some other embodiments, S3 further includes preparing the microporous layer slurry, and the specific steps include:

[0048] S31: mixing the deionized water, carbon powder, polytetrafluoroethylene emulsion and dispersant and performing ultrasonic treatment;

[0049] S32: dispersing and stirring the mixture after ultrasonic treatment.

[0050] The ultrasonic treatment time in step S31 is 2 minutes, and the dispersion stirring time in step S32 is 30 minutes.

[0051] In another embodiment, the temperature of the drying treatment in step S4 is 80° C., and the drying time is 30 minutes; the temperature of the sintering treatment in step S4 is 350° C., and the sintering time is 40 minutes.

[0052] The technical solution of the present invention is further described below in conjunction with specific implementation cases.

[0053] Take a piece of untreated gas diffusion backing layer, the thickness is 144 microns, the internal resistance is 3.57 milliohms, the surface F element content is 25.11%, and the surface roughness is 7.15 microns. In this embodiment, the maximum output power of the laser equipment used is 8.5KW, and the laser power of 5%, 10%, 15% and 20% of the maximum output power is used to scan the two surfaces of the gas diffusion backing layer once. The performance parameters of the treated gas diffusion backing layer are shown in Table 1. It can be seen from the table that after laser treatment with different powers, the thickness of the gas diffusion backing layer remains basically unchanged, all between 143 and 146 microns, indicating that the laser treatment does not destroy its structure. At the same time, with the increase of laser power, the internal resistance of the gas diffusion backing layer gradually decreases, the surface F element content is significantly reduced, and the surface roughness is also significantly improved.

[0054] After the surface treatment is completed, the microporous layer slurry is prepared. The specific steps are: deionized water, carbon powder, 60% polytetrafluoroethylene emulsion and dispersant are mixed according to a preset ratio, firstly ultrasonically treated for 2 minutes, and then dispersed and stirred in a mixer for 30 minutes to obtain a uniform microporous layer slurry.

[0055] The prepared microporous layer slurry was coated on the surface of the laser-treated gas diffusion backing layer by screen printing. The coated sample was placed in an oven at 80°C for 30 minutes and then transferred to a muffle furnace for sintering at 350°C for 40 minutes to obtain a complete gas diffusion layer.

[0056] like Figure 3 The following are the results of analyzing the F content on the surface of different samples using an energy spectrometer. (a) is an untreated sample, and (b) to (e) are samples treated with 5%, 10%, 15%, and 20% laser power, respectively. The results show that with the increase of laser power, the F content on the sample surface decreases significantly, indicating that the laser treatment effectively removes excess polytetrafluoroethylene on the surface.

[0057] like Figure 4 The results of observing the surface morphology of the microporous layer of different samples using an optical microscope are shown. (a) is a gas diffusion layer prepared from an untreated sample, where obvious carbon fiber exposure can be observed; (b) and (c) are gas diffusion layers prepared after treatment with 5% and 20% laser power, respectively, where the carbon fiber exposure phenomenon is significantly improved. This shows that reducing the surface roughness of the gas diffusion backing layer through laser treatment can effectively improve the coating quality of the microporous layer.

[0058] It should be noted that when the laser power is increased to 25% of the maximum output power, the thickness of the gas diffusion backing layer is reduced to 115 microns, indicating that its structure has been destroyed. Therefore, it is more appropriate to set the laser power in the range of 5% to 20% of the maximum output power in the present invention. Within this power range, the excess polytetrafluoroethylene on the surface can be effectively removed and the surface roughness can be reduced without destroying the structure of the gas diffusion backing layer.

[0059] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a fuel cell gas diffusion layer, characterized in that: The following steps are involved: S1: using picosecond laser to perform finishing processing on the first surface of the gas diffusion backing layer; S2: performing finishing processing on the second surface of the gas diffusion backing layer using a picosecond laser, wherein the second surface is arranged opposite to the first surface; S3: coating a microporous layer slurry on one surface of the gas diffusion backing layer after finishing; S4: drying and sintering the gas diffusion backing layer coated with the microporous layer slurry to obtain the gas diffusion layer.

2. The method for preparing a fuel cell gas diffusion layer according to claim 1, characterized in that: In the step S1 and step S2, the output power of the picosecond laser is controlled to be 0.4KW-1.6KW.

3. The method for preparing a fuel cell gas diffusion layer according to claim 2, characterized in that: The number of scans of the picosecond laser in step S1 and step S2 is 1.

4. The method for preparing a fuel cell gas diffusion layer according to claim 1, characterized in that: The microporous layer slurry in step S3 includes deionized water, carbon powder, polytetrafluoroethylene emulsion and a dispersant.

5. The method for preparing a fuel cell gas diffusion layer according to claim 4, characterized in that: The steps of preparing the microporous layer slurry include: S31: mixing the deionized water, carbon powder, polytetrafluoroethylene emulsion and dispersant and performing ultrasonic treatment; S32: dispersing and stirring the mixture after ultrasonic treatment.

6. The method for preparing a fuel cell gas diffusion layer according to claim 5, characterized in that: The ultrasonic treatment time in step S31 is 2 minutes, and the dispersion stirring time in step S32 is 30 minutes.

7. The method for preparing a fuel cell gas diffusion layer according to claim 1, characterized in that: The drying temperature in step S4 is 80° C. and the drying time is 30 minutes.

8. The method for preparing a fuel cell gas diffusion layer according to claim 7, characterized in that: The sintering temperature in step S4 is 350° C. and the sintering time is 40 minutes.

9. The gas diffusion layer prepared by the method according to any one of claims 1 to 8, characterized in that: The gas diffusion layer comprises a gas diffusion backing layer and a microporous layer arranged on the surface of the gas diffusion backing layer, wherein: the surface F content of the gas diffusion backing layer is less than 25%, and the surface roughness is less than 7 microns; and no carbon fiber is exposed on the surface of the microporous layer.